2020
DOI: 10.1097/sla.0000000000004391
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Telemedicine Adoption on a Multidisciplinary Bariatric Surgery Practice During the COVID-19 Pandemic

Abstract: Objective: This study aims to show how full-time telemedicine adoption has impacted patient visit volume and attendance in a comprehensive metabolic and weight loss center. Summary Background Data: Elective surgical practices have been profoundly impacted by the global COVID-19 pandemic, leading to a rapid increase in the utilization of telemedicine. The abrupt initiation of audio-video telehealth visits for all providers of a multidisciplinary clinic on March 19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 19 publications
1
34
0
Order By: Relevance
“…In this study, from Italy the authors reported a 24% no-show rate with the implementation of telemedicine seemingly due to technology-related factors as well as lack of digital literacy [ 18 ]. On the other hand, another study conducted at a well-established comprehensive bariatric center found the no-show rate to be decreasing in the post-pandemic era [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, from Italy the authors reported a 24% no-show rate with the implementation of telemedicine seemingly due to technology-related factors as well as lack of digital literacy [ 18 ]. On the other hand, another study conducted at a well-established comprehensive bariatric center found the no-show rate to be decreasing in the post-pandemic era [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study has implications for clinical practice. Considering that although telemedicine implementation is not yet widely adopted [32], its adoption was shown to increase follow-up visit volume [33]; protocols for monitoring patients after metabolic and bariatric surgery should implement measures that enable remote follow-up of these patients during confinement to minimize its detrimental effects on emotional distress, diet, and weight outcomes. Our patients were followed remotely during confinement and, still, increased levels of emotional distress were associated with EDF consumption, which was, in turn, associated with worse BMI outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, during this time, highly contagious COVID-19 variants were circulating; however, mass vaccination efforts were beginning to move forward. Some preliminary evidence has found that bariatric patient follow-up rates may have been improved by a shift to telemedicine during the pandemic [ 46 ]. However, other studies suggest that the pandemic may have increased the risk of adverse physical and mental health outcomes for bariatric patients [ 47 - 50 ].…”
Section: Discussionmentioning
confidence: 99%